Identifying Hidden Factors Affecting Household Solid Waste Generation for an Effective Waste Management System (Proceedings of the World Conference on Waste Management, 2019)
Current urbanization, rapid economic growth and changes in the consumption pattern are burning issues faced by the developing countries on solid waste management. Proper solid waste management should be implemented with the urbanization in order to manage the households’ waste generation. There should be proper solid waste management strategies and techniques within the micro level. Identifying households’ hidden factors affecting towards waste generation in households led the foundation to develop an accurate waste management system. The study was administrated in the Colombo district using 335 households taken from Maharagama Urban Council and Kotikawatta-Mulleriyawa Pradeshiya Sabha. Solid waste generation in the household based on the low, middle and high income level was 0.12 Kg/person/day, 0.17 Kg/person/day and 0.25 Kg/person/day. The study found that hidden factors for waste generation in households were family consumption pattern, family background, nature of the waste collection and ways of treating waste. Recognizing the opportunities and challenges within the area provides a clear path for waste management.
Keywords: Hidden Factors; Per Capita; Households; Solid Waste; Waste Management